The existence of a classical solution to the mixed problem for a linear second-order hyperbolic equation - Mitropolskiy, Yu. A.; Khoma, L. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The paper deals with the problem of solvability of the mixed problem for a linear second-order hyperbolic partial differential equation. The minimal necessary and sufficient conditions for the existence of a unique classical solution to this problem are established.